Pertanggungjawaban Pidana terhadap Pelaku Penyebaran Foto Asusila di Media Sosial: Studi Putusan Nomor 12/Pid.B/2025/PN.Tdn - Eva Maria Tinambunan; Rahmiati; Fikry Latukau (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
The non-consensual dissemination of indecent photographs through social media violates dignity and privacy and may cause psychological harm to victims. This normative legal research examines Decision Number 12/Pid.B/2025/PN.Tdn using statutory, case and conceptual approaches. The findings show that the defendant satisfied the elements of Article 45 paragraph (1) in conjunction with Article 27 paragraph (1) of the Electronic Information and Transactions Law applicable when the case was decided, as well as the requirements of criminal liability, namely capacity for responsibility, intent and the absence of grounds excluding liability. No new detention was ordered because the defendant was already serving another sentence and remained under state custody. From a victim-protection perspective, the sentence considered the harm suffered by the victim, but recovery remained incomplete because the judgment contained no restitution, content-removal order, psychological recovery measure, or specific measure to prevent further dissemination. The more recent standards under Law Number 3 of 2026 on the Protection of Witnesses and Victims reinforce the need for victim-oriented recovery in criminal adjudication.